Concordance between a gastrointestinal consultant radiologist, a consultant radiologist and qualified reporting radiographers interpreting abdominal radiographs. Issue 2 (March 2023) - Moth, A.; Benning, J.; Glover, J.; Brown, V.; Pittock, L.; Woznitza, N.; Piper, K.
Abstract: Introduction: Radiographers can accurately report musculoskeletal and chest radiographs, but there is paucity of research comparing the performance of reporting radiographers (RRs) with consultant radiologists when interpreting and reporting abdominal radiographs. This study assessed interobserver agreement in the clinical setting between reporting radiographers and a consultant radiologist compared to an expert gastrointestinal radiologist in a District General Hospital. Major discordant reports affecting patient management were also examined. Methods: 126 abdominal radiographs reported by 3 RRs in clinical practice were randomly selected and reported by a consultant radiologist and index gastrointestinal radiologist. The reports of the RRs and consultant radiologist were compared against the reports made by the index radiologist for agreement by a colorectal consultant surgeon. All 126 reports were scored as being in either complete agreement, minor disagreement or major disagreement which would have resulted in a change to patient management. Results: There was no significant difference in overall agreement between the consultant radiologist (CR) and RRs when compared to the index radiologist (CR: n = 90/126, 71.4% and RRs: n = 94/126, 74.6%. p = 0.57). Major disagreements were found, but there was no significant difference between both groups (CR: n = 23/126, 18.3% and RRs: n = 17/126, 13.5%. p = 0.30). Conclusion: RRs can report abdominal radiographs to a comparable level of agreement as a consultant radiologist in the clinical setting. There was no significant difference in reports deemed to affect patient management. Implications for practice: This study addresses the gap in assessing the performance of RRs reporting abdominal radiographs. This small scale study indicates that radiographers could provide additional support in the reporting of abdominal radiographs. This would help to reduce radiologist workload and enhance the role of the reporting radiographer. Classification: Agreement between reporting radiographers and radiologists interpreting and reporting abdominal radiographs.